Developing E-cigarette friendly smoking cessation services in England: staff perspectives - Hannah Farrimond; Charles Abraham (BMC, 2018)
Abstract Background Public health leadership in England has taken a distinctive international stance by identifying the potential public health benefit of e-cigarettes for smoking cessation. This includes the development of a ground-breaking set of national guidelines for developing e-cigarette friendly stop smoking services. However, little is known about the views of staff engaged within these services and whether or how such services are becoming e-cigarette friendly. This study aimed to investigate the uptake and usage of e-cigarette guidance, from the perspective of those enacting tobacco cessation interventions 'on the ground'. Methods Qualitative semi-structured interviews were conducted with 25 cessation service staff, including advisors (n = 15), managers (n = 5) and commissioners (n = 5) from eight different services in the South-West of England, UK. A thematic analysis of the transcripts was conducted using NVivo software. Results Although some stop smoking services labelled themselves e-cigarette friendly, there was no consensus over what this should entail. For some, this meant active engagement, such as working with local vape shops, and in the case of one service, offering e-cigarettes through a voucher scheme to disadvantaged groups. For others, an e-cigarette friendly service was conceptualized in a passive sense, as one which welcomed service users using e-cigarettes. Many services did not use the 'e-cigarette friendly' claim in their branding or promotional material. Several discursive themes underlay differing staff attitudes. Those more reluctant to engage framed this in terms of their 'duty of care', with concerns focusing on the addictiveness of nicotine, lack of medically licensed product and ongoing scientific controversy. Those motivated to engage drew on a discourse of social justice goals and 'doing things differently' in relation to lower socio-economic status smokers, those with mental health issues and other vulnerable groups. Strong public health leadership was also identified as a key factor in changing staff attitudes towards e-cigarettes. Conclusions On-the-ground enactment of e-cigarette friendly services is varied as well as reflective of the wider policy and regulatory environment. Although the context of English stop smoking services is one of austerity and change, there are opportunities for active engagement with e-cigarettes to achieve overall cessation goals. For this to occur, training, policy consistency and sharing best practice are needed.